Properties of the HtrA Protease From Bacterium Helicobacter pylori Whose Activity Is Indispensable for Growth Under Stress Conditions - Zarzecka, Urszula; Modrak-Wójcik, Anna; Figaj, Donata; Apanowicz, Malgorzata; Lesner, Adam; Bzowska, Agnieszka; Lipinska, Barbara; Zawilak-Pawlik, Anna; Backert, Steffen; Skorko-Glonek, Joanna (Frontiers in Microbiology, 2019)
The protease high temperature requirement A from the gastric pathogen Helicobacter pylori (HtrAHp) belongs to the well conserved family of serine proteases. HtrAHp is an important secreted virulence factor involved in the disruption of tight and adherens junctions during infection. Very little is known about the function of HtrAHp in the H. pylori cell physiology due to the lack of htrA knockout strains. Here, using a newly constructed ΔhtrA mutant strain, we found that bacteria deprived of HtrAHp showed increased sensitivity to certain types of stress, including elevated temperature, pH and osmotic shock, as well as treatment with puromycin. These data indicate that HtrAHp plays a protective role in the H. pylori cell, presumably associated with maintenance of important periplasmic and outer membrane proteins. Purified HtrAHp was shown to be very tolerant to a wide range of temperature and pH values. Remarkably, the protein exhibited a very high thermal stability with the melting point (Tm) values of above 85°C. Moreover, HtrAHp showed the capability to regain its active structure following treatment under denaturing conditions. Taken together, our work demonstrates that HtrAHp is well adapted to operate under harsh conditions as an exported virulence factor, but also inside the bacterial cell as an important component of the protein quality control system in the stressed cellular envelope.